Pragmalinguistic Analysis Of Selected Translations Of Surah Yusuf In The Holy Quran - Hidyan, Saad Hatem Hasan (2018)
Dealing with the translatability of Speech Acts (SAs) in religious texts was the main focus of the present thesis. The present research carefully examined, detected, and analysed the presence of different speech acts in accordance with Austin’s and Searle’s classifications in the translation of Surah Yusuf. The verses in Surah Yusuf have been classified based on Austin’s and Searle’s categorisation. Moreover, they have been subject to a pragmatic analysis based on their associated contextual situations. The study consisted of six chapters. The first chapter presented the introduction, the statement of the problem, the objectives and the questions of the study.